International collaboration in local government studies: a bibliometric analysis - Jing, Yijia; Fan, Wenxue; Liu, Meijun; Xu, Jingyuan (Local government studies, 2024)
International collaboration in public administration research is getting popular, reflecting growing globalisation in PA practices and the strength of collaborative knowledge production. This article examines international collaboration in 1,550 research articles published in Local Government Studies (LGS) between 1974 and 2022. The bibliometric analysis shows international coauthorship in LGS appeared in 1980 and increased to 23.08% among articles published in 2022. While international collaboration in LGS has been lower than that of average PA journals, the gap has been shrinking. Regression analysis indicates that LGS articles with international coauthorship yield greater scientific impacts. This study argues that further internationalisation of LGS and other PA journals with a focus on local issues demands theoretical and methodological breakthroughs in comparative local studies, as well as a wider and more balanced distribution of authors. This article also calls for further studies of the quality effects of international collaboration.